FRAMING ANALYSIS PEMBERITAAN AKSI PENEMBAKAN MUSLIM CHRISTCHURCH NEW ZEALAND DI MEDIA ONLINE BBC - Moh. Yunus (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
In this article, the authors chose to do a framing analysis built by western media in the Muslim shootings that took place in New Zealand. The media that the authors of the analysis are online media, BBC. After framing the author found several facts that, the BBC media always tuck in every beginning of the headline (which is related to the event) by using the sentence Christchurch Shootings. The BBC media also picked up a story of a hero in Naaem Rashid, one of the victims who fought against the shooter before being killed. This media also criticized several policies on the legality of possession of firearms in New Zealand and criticism of several social media that ‘already’broadcasted videos containing shooting content and delays in some of the social media in removing videos that had spread. BBC media did not mention that this act was an act of terrorism or even called Brenton Tarrant - the Actor of the Shooting - as a terrorist. In fact, this media does not mention the issue of religion which is one of the motives for the shooting carried out by Brenton. The media also did not mention victims based on their religion. This shows that the BBC media does not want to bring up the religious issue which is one of the factors in the shooting.